Discovering students' responses using flipped classroom model through reading comprehension teaching - Praba Lucya Suryana; Totoh Tauhidin Abas; Nina Puspitaloka (English, 2021)
Recently there has been a spate of interest on the flipped classroom that is the new learning model on education. Flipped classroom learning model is when the teacher giving material online through internet (outside the classroom). Students’ learning to understand the topic or material at home and conducting discussions or questions and answers, where the teacher answers the difficulties of students related material in the classroom. The teacher ask students with some of questions to check the students’ comprehension. In this research, focused on Flipped classroom model in teaching reading comprehension: students responses. The purpose of this research to find out the flipped classroom learning model is incorporated technology assisted and then to find out the flipped classroom learning model responded balance by students’. In research site and participant the researcher involved 36 students, 6 students as participants from second grade of Senior High School 1 Karawang West Java, with study objective sampling by using qualitative narrative inquiry method. To collect the data the researcher used three instrument that is reflective journal, interview and documentation. For data analysis technique the researcher used thematic analysis by Braun & Clark (2006) which is read the data deeply, transcribe, code, categorize, and interpret the data to analyze the data. The result of the research shown that students have positive responses. There are 5 students’ have the same positive responses that is students’ more comfortable to learning, get better understanding the material, make them active discuss in classroom. But 1 of students’ have a negative responded that is the condition of the classroom not conducive make her not really understood the material. It can be concluded that the flipped classroom learning model responded balance by students. The most of students more comfortable to learning the material first at home before teaching and learning in the classroom make them understand better, students more active to express their though in discussion session and also the process of learning was more interesting and helpful of them.